MODEL DISCOVERY LEARNING DAN MODEL INQUIRY LEARNING - M. Ramli, M. Ramli; Mardhiyatirrahmah, Liny (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2025)
This article aims to examine in depth two active learning models widely applied in modern education: Discovery Learning and Inquiry Learning. Using a qualitative approach with a literature review method, the author reviews the concepts, characteristics, steps, and advantages and disadvantages of each model based on academic literature. Discovery Learning emphasizes students' independent exploration process in discovering concepts through direct experience, while Inquiry Learning encourages students to engage in a systematic scientific investigation process to answer a problem. The results of the study indicate that both models are able to improve students' critical thinking and analytical skills, and independent learning. In addition, the application of these two approaches can also foster students' curiosity and active involvement in the learning process, thereby creating a more meaningful and sustainable learning experience. This article is expected to serve as a reference for educators in designing learning that is adaptive, participatory, and relevant to the demands of the 21st century